Imbalanced Folate and Vitamin B12 in the Third Trimester of Pregnancy and its Association with Birthweight and Child Growth up to 2 Years. Issue 2 (11th December 2021) - Obeid, Rima; Eussen, Simone J.P.M.; Mommers, Monique; Smits, Luc; Thijs, Carel
Abstract : Scope: Folic acid supplementation during pregnancy may lead to an imbalance when vitamin B12 intake is low (folate trap) and may affect child's growth. Methods: The authors study the association between third trimester maternal intakes of folate and B12 and birthweight and postnatal growth of 2632 infants from the KOALA Birth Cohort Study. Plasma vitamin biomarkers are measured in 1219 women. Results: Imbalanced total intakes (folate > 430 µg day −1 combined with B12 < 5.5 µg day −1 ) are not associated with birthweight [β adj (95% CI) = –14.87 (–68.87, 39.13)] compared with high intakes of both. Imbalanced intake is associated with a lower z score of weight at 1–2 years [β adj = –0.14 (–0.25, –0.03)]. Having red blood cell folate > 745 nmol L −1 and plasma B12 < 172 pmol L −1 is not associated with birthweight [β adj = –7.10 (–97.90, 83.71) g]. Maternal dietary B12 intake [β adj = –9.5 (–15.6, –3.3)] and plasma methylmalonic acid [β adj = 234 (43, 426)] are associated with birthweight. Conclusion: Low maternal dietary B12 intake and elevated methylmalonic acid rather than imbalanced vitamins are associated with higher birthweight, suggesting that low maternal B12 can predispose the infants for later obesity. Abstract : In the KOALA Birth Cohort Study, the authors find that high total folate intake combined with low intake of B12 is not associated with birth weight. Low dietary B12 intake and elevated methylmalonic acid rather than imbalanced folate to B12 are associated with higher birth weight, suggesting that low maternal B12 can predispose the infants for later obesity.